2023
DOI: 10.1038/s41467-023-40281-2
|View full text |Cite
|
Sign up to set email alerts
|

Incandescent temporal metamaterials

J. Enrique Vázquez-Lozano,
Iñigo Liberal

Abstract: Regarded as a promising alternative to spatially shaping matter, time-varying media can be seized to control and manipulate wave phenomena, including thermal radiation. Here, based upon the framework of macroscopic quantum electrodynamics, we elaborate a comprehensive quantum theoretical formulation that lies the basis for investigating thermal emission effects in time-modulated media. Our theory unveils unique physical features brought about by time-varying media: nontrivial correlations between fluctuating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 90 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…469 Building upon this basis, it has been recently demonstrated that a proper treatment of the interaction Hamiltonian paves the way for a comprehensive theoretical framework to bridge two fundamental and currently very active areas of research in the fields of nanophotonic engineering and physics, namely, time-varying media and thermal emission. 73 ■ TIME-DEPENDENT THERMAL EMISSION:…”
Section: Acs Applied Optical Materialsmentioning
confidence: 99%
“…469 Building upon this basis, it has been recently demonstrated that a proper treatment of the interaction Hamiltonian paves the way for a comprehensive theoretical framework to bridge two fundamental and currently very active areas of research in the fields of nanophotonic engineering and physics, namely, time-varying media and thermal emission. 73 ■ TIME-DEPENDENT THERMAL EMISSION:…”
Section: Acs Applied Optical Materialsmentioning
confidence: 99%
“…Temporal modulation is capable of releasing these fields, forming the dual of a spatial grating, which consists of a narrowband peak fixed at a given frequency, but whose radiation scans all wave-vectors, from near to far fields. 213…”
Section: ■ Enz Media For Time-varying Photonicsmentioning
confidence: 99%
“…Time-modulation of the refractive index breaks key assumptions in the usual form of the fluctuation dissipation theorem and Kirchhoff’s law, which form the basis of thermal emitters. Therefore, while thermal fluctuating currents are typically uncorrelated in frequency and space for conventional thermal emitters, time modulation leads to secondary currents that are correlated in frequency and space, opening the door to thermal emission with enhanced coherence and nontrivial photon correlations . Furthermore, energy can be either pumped into a material or retracted from it as it is modulated in time, enabling “active” thermal emitters radiating outside the blackbody spectrum, and acting as heat engines .…”
Section: Enz Media For Time-varying Photonicsmentioning
confidence: 99%
See 2 more Smart Citations